2015
DOI: 10.1111/ajt.13317
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Transplantation Using Organs From Donors Infected or Colonized With Carbapenem-Resistant Gram-Negative Bacteria

Abstract: Donor-derived infections due to multidrug-resistant bacteria are a growing problem in solid organ transplantation, and optimal management options are not clear. In a 2-year period, 30/214 (14%) recipients received an organ from 18/170 (10.5%) deceased donors with infection or colonization caused by a carbapenemresistant gram-negative bacteria that was unknown at the time of transplantation. Among them, 14/30 recipients (47%) received a transplant from a donor with bacteremia or with infection/colonization of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
116
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(125 citation statements)
references
References 30 publications
2
116
1
1
Order By: Relevance
“…Cohort studies with patients who received a transplant from donors with sepsis have identified that transmission did not occur among those who received adequate antibiotic therapy for at least seven days. (18)(19)(20) For this reason, the OPOs in Parana carefully analyze the clinical outcomes of the patients along with CIH-DOTT professionals in order to verify the viability of the donation for these cases. (16) Regarding the reasons for not donating organs among the eligible donors, family refusal ranked first with 37.3%.…”
Section: Discussionmentioning
confidence: 99%
“…Cohort studies with patients who received a transplant from donors with sepsis have identified that transmission did not occur among those who received adequate antibiotic therapy for at least seven days. (18)(19)(20) For this reason, the OPOs in Parana carefully analyze the clinical outcomes of the patients along with CIH-DOTT professionals in order to verify the viability of the donation for these cases. (16) Regarding the reasons for not donating organs among the eligible donors, family refusal ranked first with 37.3%.…”
Section: Discussionmentioning
confidence: 99%
“…However, 3 of the 6 patients who were not immediately treated with appropriate therapy developed a post-transplant CRGN infection. 45 Additional studies are required to better delineate the role of pre-transplant screening for CRE among SOT candidates and donors, as well as the impact of pretransplant colonization on outcomes, including patient and graft survival. If a donor or recipient is known to be colonized or infected with CRE prior to transplantation, it is recommended that a risk-benefit evaluation be make, taking into account the source of positive donor cultures and the organ being transplanted.…”
mentioning
confidence: 99%
“…Although bacterial transmission from the donor population is rare: Eight donors with P/P bacteria transmission affecting nine recipients from more than 8,000 deceased donors, resulting in three deaths, in 2012) [14]. The national data suggest that gram-negative bacteria account for about 80% of transmissions to recipients, and a significant percentage of these are recognized after ruptured mycotic aneurysms resulting in recipient graft loss or death or both [15]. A particular concern has been with the use of organs from donors with heavily contaminated surgical sites (the open abdomen), as this has been associated with a recognized risk of transmission of infection to an organ recipient [16,17].…”
Section: Bacteriamentioning
confidence: 99%